Blade runner - Redmond, Sean, 1967- (Constellations (Leighton Buzzard, England), 2016)
Ridley Scott's 1982 film Blade Runner is now widely recognized as an undisputed masterwork of science fiction cinema and one of the most influential films released in the last forty years. Yet on its original release it was both a critical and commercial failure, criticized for its perceived prioritizing of style over content and a narrative that did not deliver the anticipated high octane action that its star casting and large budget normally promise. How did a film that was removed from circulation within a month of its premiere come to mean so much to modern audiences and provide such a ric.